Campus journalism and school paper advising - Cruz, Ceciliano Jose. (Manila, Philippines : REX Book Store, 2010)
Campus Journalism and School Paper Advising (Second Edition) is a skill book based on a bilingual course of study prepared by the Division of City Schools, Manila. Each unit is preceded by expected outcomes to guide new teachers and paper staff advisers in the preparation of their lesson plans. The book exposes the students to different types of journalistic writing such as news, editorials, columns, features and sport. Included also are the other phases of work such as headline writing, copy reading, proofreading, layout, photojournalism, cartooning, typography, and the legal ethics of Journalism. Useful and practical study helps and writing exercises are placed at the end of every unit to enhance student's understanding of the lesson and test their skills
Unit I. High School Publication - A Brief History -- Unit II. Journalism in General -- Unit III. Letterpress Printing from Reporter to Reader -- Unit IV. Elements that Make News -- Unit V. Writing the Lead -- Unit VI. Writing the News Story -- Unit VII. Writing Headlines -- Unit VIII. Development Communication -- Unit IX. Science Writing -- Unit X. Technical Writing -- Unit XI. Writing the Editorial -- Unit XII. Writing Editorial Columns -- Unit XIII. Cartooning -- Unit XIV. Writing Features -- Unit XV. Writing the Interview -- Unit XVI. Writing the Sports Story -- Unit XVII. Preparing the copy and copyreading -- Unit XVIII. Reading Proofs -- Unit XIX. Layout or Makeup -- Unit XX. Photojournalism -- Unit XXI. Printing and typography -- Unit XXII. Computer Printing -- Unit XXIII. Ethics and laws of the press -- Unit XXIV. The newspaper law -- Unit XXV. A style guide -- Unit XXVI. Broadcast media -- Unit XXVII. Scriptwriting.
Includes bibliographical references and indexes.
Keywords: JOURNALISM -- HANDBOOKS -- MANUALS